The Pharmacology of Visual Hallucinations in Synucleinopathies - Russo, Mirella; Carrarini, Claudia; Dono, Fedele; Rispoli, Marianna Gabriella; Di Pietro, Martina; Di Stefano, Vincenzo; Ferri, Laura; Bonanni, Laura; Sensi, Stefano Luca; Onofrj, Marco (Frontiers in Pharmacology, 2019)
Synucleinopathies include Parkinson’s disease and Dementia with Lewy Bodies, where visual hallucina-tions (VH) are so frequent to lead to the conclusions that if hallucinations do not appear during the dis-ease course, diagnosis should be challenged. VH may be early and simple and late and complex, includ-ing hallucinatory states which represent an unmet need for treatment. Our review analyses old and re-cent hypotheses on the mechanisms of VH and discusses a number of drugs involved in production and suppression the VH, in order to complete the hypothesis of mechanisms. Recent models of VH are cen-tered on decoupling of the Default Mode Network (DMN), which is released in these disorders from the fronto-parietal control and from salience networks, resulting in perception of priors stored in uncon-scious memory. The release of DMN supposedly releases the intrinsic narrative of DMN. The thalamus represents a powerful control relay according to recent theories on “cognitive thalamus”. The networks involved imply practically all relevant neurotransmitters, including glutamic acid, Gamma-Aminobutyric Acid (GABA), dopamine, serotonin, acetylcholine. Actually, evidence-based medicine can only rely on clozapine, an old drug very effective but burdened by several side effects. According to the models, serotonergic, glutamatergic, GABAergic and dopaminergic pathways should be investigated in order to develop possible new treatment drugs. According to a possible model of thalamic dysfunction, also drug acting on calcium channels might find a role. Our review analyses also the agonist and antagonist drugs and reports on drugs inducing hallucinations as side effects, which should be taken into account when managing hallucinating disorders in these patients, who are also carriers of many comorbidities.